2005
DOI: 10.1038/sj.emboj.7600521
|View full text |Cite
|
Sign up to set email alerts
|

Conditional MLL-CBP targets GMP and models therapy-related myeloproliferative disease

Abstract: Chromosomal translocations that fuse the mixed lineage leukemia (MLL) gene with multiple partners typify acute leukemias of infancy as well as therapy-related leukemias. We utilized a conditional knockin strategy to bypass the embryonic lethality caused by MLL-CBP expression and to assess the immediate effects of induced MLL-CBP expression on hematopoiesis. Within days of activating MLL-CBP, the fusion protein selectively expanded granulocyte/ macrophage progenitors (GMP) and enhanced their selfrenewal/prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 45 publications
2
87
0
Order By: Relevance
“…However, no disease was developed in EHKI DNeo mice during the long-term observation period (Figure 2a, thin lines), indicating that the acquired expression of E2A-HLF per se is insufficient for the development of leukemia. This finding is in line with previous reports showing that iKI mice of other leukemogenic transcription factor chimeras, such as AML1-ETO and MLL-CBP, did not show hematopoietic disorders, and secondary mutations induced by N-methyl-N-nitrosourea or irradiation were required to induce a fully malignant phenotype (Higuchi et al, 2002;Wang et al, 2005). In this study, to introduce additional gene alterations, we used RIM, as it not only …”
Section: Discussionsupporting
confidence: 85%
“…However, no disease was developed in EHKI DNeo mice during the long-term observation period (Figure 2a, thin lines), indicating that the acquired expression of E2A-HLF per se is insufficient for the development of leukemia. This finding is in line with previous reports showing that iKI mice of other leukemogenic transcription factor chimeras, such as AML1-ETO and MLL-CBP, did not show hematopoietic disorders, and secondary mutations induced by N-methyl-N-nitrosourea or irradiation were required to induce a fully malignant phenotype (Higuchi et al, 2002;Wang et al, 2005). In this study, to introduce additional gene alterations, we used RIM, as it not only …”
Section: Discussionsupporting
confidence: 85%
“…This 'wave effect' is highly reproducible and is commonly observed in serial replating studies. 30,31 Cytospin analysis of bone marrow cells after the third methylcellulose plating demonstrated increased progenitor cells in Bid À / À cultures ( Figure 4a). The black arrow denotes a neutrophil, the terminally differentiated myeloid cell type.…”
Section: Resultsmentioning
confidence: 99%
“…17 Thus, histologic and immunophenotypic analysis show that MLL-AF9 and MLL-AF9 combined with FLT3-ITD induce a similar leukemia in this system. Recent experiments have shown that leukemias derived from MLL fusion proteins 14,18 demonstrate expansion of a GMP-like population at the expense of other myeloid progenitors. In order to verify that this phenomenon occurs when a second oncogene is introduced along with MLL-AF9, we performed flow cytometry on bone marrow from normal and leukemic mice.…”
Section: Mll-af9 and Mll-af9/flt3-itd Mice Develop Similar Myeloid Lementioning
confidence: 99%
“…Similarly, a conditional MLL-CBP knock-in mouse that recapitulates t-AML induced by the t(11;16) requires chemical or irradiation-induced mutagenesis for generation of a fatal myeloproliferative disease or leukemia. 18 Furthermore, bone marrow transplant models progress to oligoclonal leukemias pointing to the need for cooperating mutations in MLL-induced leukemogenesis. 19 Recent hypotheses as to the multistep nature of leukemogenesis suggest mutant signaling molecules are good candidates for cooperation with DNA-binding fusion oncogenes during leukemogenesis.…”
Section: Introductionmentioning
confidence: 99%